Aproximaciones metodológicas a una colección de sermones medievales: San Vicente Ferrer y el manuscrito del Colegio del Corpus Christi - Ferrari, Mariano (Actas y comunicaciones del Instituto de Historia Antigua y Medieval)
Vicente Ferrer was one of the most outstanding preachers of the Medieval West. The study of his sermons gives us the opportunity to recognize some of the main characteristics that this genre had in the Iberian peninsula towards the end of the Middle Ages. The sermons of the saint, which are preserved at the Real Colegio-Seminario del Corpus Christi of Valencia, provides access to a homiletic corpus of over 180 sermons. Studying these ones, we can get a significant sample of the main contents of Ferrer’s speech, and ask what place his apocalyptic preaching occupies in them.